Management of Facilities and Infrastructure as an Indicator of Student Skills at SMK N 2 Serang City - Irwanto Irwanto; Bayu Saputra (Program Studi Magister Manajemen Pendidikan)
In accordance with the purpose of vocational education, which is to prepare novice workers for the needs of the industrial world, especially industries that have collaborated with the SMK. SMKN 2 Serang City must look at the conditions and situations in the industry so that SMK graduates can later be absorbed into the DUDI. The new trend for SMK must strive for comprehensive reform and seriously advance SMKN 2 Kota Serang is not only a dream but there is no certainty in the achievement of these graduates of SMKN 2 Kota Serang. At the level of the learning process, a paradigmatic shift is needed in carrying out innovations or new breakthroughs in the learning process in the SMK. Vocational education in Indonesia is a shortcut to filling DUDI's workforce while reducing the level of unemployment with skills in accordance with their respective expertise. Indicators in practical learning based on BMW, namely work, continuing education and entrepreneurship according to their expertise. As long as one condition has to be fulfilled, for example establishing a collaboration between SMKN 2 Kota Serang and DUDI and not only cooperating in the form of an MOU but the industrial world should be able to provide an experience to the world of vocational education, and vice versa. For example, industry share knowledge at SMKN 2 Kota Serang and SMKN 2 Kota Serang should also seek experience in industry. Whether it's teaching staff (teachers, technicians) and students of SMKN 2 Kota Serang.Key words: SMK, business world and industry, facilities, infrastructureDOI : 10.23960/jmmp .v9.i1.202103